Polyurethane porous foam loaded CdS / MIL-101 (Fe) photosensitizer preparation method, product and application
By combining CdS with the porous MOF framework structure and performing secondary solid loading, the problem of low particle agglomeration and catalytic CO2 reduction efficiency of CdS photosensitizer during the catalysis process is solved, rapid solid-liquid separation of the catalyst and efficient CO2 reduction are achieved, and the recovery efficiency of powder materials is improved.
Patent Information
- Application Number
- CN202411771598.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-25
AI Technical Summary
The particle agglomeration of CdS photosensitizer during the catalytic process leads to low catalytic CO2 reduction efficiency, and complex recycling of powder materials and high loss.
The MOF skeleton structure with a porous high specific surface area is combined with CdS, and the loaded MIL-101 (Fe) is synthesized by impregnation method, and the secondary solid loading of the CdS active components is performed by liquid phase method to improve the transfer efficiency of photogenerated charges and realize rapid solid-liquid separation of the catalyst.
The distribution rate of CdS in the pores is improved, the CO2 absorption and reduction capacity is enhanced, the problem of poor recovery rate of powder materials is solved, and the solid biomass yield is improved.
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method, product and application of a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer, which utilizes a porous MOF skeleton structure with a high specific surface area to strengthen the reduction effect of CdS on CO2 and is used in the field of sewage treatment. Background Art
[0002] The exploitation and utilization of fossil fuels, and the large amount of carbon dioxide produced by human life and production activities have accelerated the rate of global warming. Photocatalytic conversion of carbon dioxide into high-value-added fuels and chemicals seems to be a feasible strategy to solve the energy and environmental crises at the same time. Photocatalytic CO2 reduction is a process that uses light energy to drive catalysts to convert CO2 into renewable hydrocarbon fuels. This technology can not only save fossil resources such as oil, natural gas and coal, but also turn waste into treasure, effectively reduce the harm of CO2 to the environment, and has significant economic and environmental benefits.
[0003] Inorganic nano-semiconductor materials have rich photophysical and chemical properties and excellent photostability, and are used as photosensitizers for artificial photosynthesis carbon fixation. Among them, CdS is a visible light responsive photosensitive material with a suitable band gap and conduction band position, which can effectively adsorb CO2 and convert it into more active negatively charged CO2 species. However, the aggregation of CdS nanoparticles and the problem of photocorrosion during the photocatalytic process will limit the application of photocatalytic CO2 reduction. In order to further solve these problems, the construction of porous nanostructures can expose more reactive sites and effectively inhibit the recombination of electrons and holes.
[0004] MOFs materials have high specific surface area and rich porosity, and their structure and performance are adjustable, and they are widely used in the field of adsorption / separation. If CdS nanoparticles can be composited with MOFs, the open pore structure of MOFs can be fully utilized to expand the contact area between MOFs and CdS, enhance the synergistic effect between the two, and improve the transfer efficiency of photogenerated charges, thereby providing more catalytic active sites for reducing CO2.
[0005] In addition, the recovery problem of powder photocatalysts is also a major factor affecting their large-scale application. Immobilization of powder materials is currently the most effective processing technology. However, traditional carriers such as silica particles, bentonite, mesoporous molecular sieves, etc. cannot completely solve the problem of poor recovery rate of powder catalysts. Based on these problems, this patent application adopts a two-step method, namely, first synthesizing the supported MIL-101 (Fe) by impregnation method, and then performing secondary immobilization of CdS active components by liquid phase method, and utilizing the synergistic effect between composite materials to increase the charge transfer rate and promote photocatalytic CO2 reduction. At the same time, the supported material can be quickly separated from water, solving the problem of complex recovery and high loss of powder materials. Summary of the invention
[0006] In view of the problems of particle agglomeration of CdS photosensitizer and low catalytic CO2 reduction efficiency during the catalytic process, the present invention aims to provide a method for preparing a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer.
[0007] Another object of the present invention is to provide a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer product prepared by the above method.
[0008] Another object of the present invention is to provide an application of the above product.
[0009] The purpose of the present invention is achieved by the following scheme: a method for preparing a polyurethane porous foam-supported CdS / MIL-101 (Fe) photosensitizer, which utilizes the structural advantages of MOFs materials to enhance the photoinduced electrons generated by CdS to promote the reduction of CO2, and immobilizes it on a porous carrier to achieve rapid solid-liquid separation of the catalyst, specifically comprising the following steps: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, soak it in ultrapure water for 24 hours, dry it, and set aside; (2) Dispersing MIL-101(Fe) powder in anhydrous ethanol according to a certain mass ratio, adding the activated polyurethane sponge in (1), placing in an ultrasonic reactor for ultrasonic dispersion, and then placing in a constant temperature shaker for oscillation reaction, controlling the temperature, oscillation rate and time; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution in a certain proportion, then add 1 mM thioacetamide solution and 0.05 g surfactant dropwise according to the nCd(NO3)2:n thioacetamide molar ratio of 1:1, stir and mix for 2 h, and then stand at room temperature for aging, controlling the water bath temperature and aging time; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
[0010] The mass ratio of the MIL-101(Fe):polyurethane porous foam is 1:(5-20); The temperature, shaking rate and time are 25-40°C, 100-250 r / min and 2-6 h respectively; The molar ratio of Cd(NO3)2 to MIL-101(Fe) is (1-8):1, and the surfactant is any one of polyethylene glycol and CTAB; The water bath reaction temperature and time are 60-90° C. and 3-6 h.
[0011] The invention provides a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer, which is characterized in that it is prepared according to any of the above methods.
[0012] The invention provides an application of a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer in photocatalytic reduction of CO2 to produce methanol.
[0013] The CO2 reduction performance of CdS / MIL-101(Fe) photosensitizer was tested in a photocatalytic reduction CO2 reaction device. A 300W Xe lamp was used as the reaction light source. 1g of the supported photosensitive catalyst and 100mL of Na2SO3 and NaOH solution were added to the reactor, mixed and stirred, and CO2 gas was introduced at a certain flow rate. After 30 minutes of dark treatment, the light source was turned on, and a certain amount of the reaction solution was taken every 30 minutes to measure the methanol content.
[0014] In order to solve the problem of particle agglomeration and low efficiency of catalytic CO2 reduction of CdS photosensitizer during the catalytic process, MOFs are used as catalysts, and their structural advantages are used to increase the distribution rate of CdS in the pores, stimulating CO2 absorption and reduction. Further, after being immobilized on porous carriers, the problem of high loss rate of powder materials in recycling can be solved, the yield of solid biomass can be increased, and valuable C2 + Chemical synthesis, which has great guiding significance for practical applications.
[0015] Based on the large specific surface area, porosity and a large number of unsaturated active sites of MOFs materials, CO2 can be directly captured from the air. The highly efficient photocatalytic CO2 reaction system constructed can effectively promote the charge transfer at the interface of the composite system, improve the CdS electron mass transfer process, and further improve the CO2 photoreduction ability. At the same time, by simply loading the active component CdS / MIL-101 (Fe) onto the porous foam carrier through in-situ immobilization, the loading rate of the composite material can be further increased, the photosynthetic carbon fixation rate can be accelerated, and the loaded material can solve the problem of difficult recycling of powder materials in actual working conditions, and quickly perform solid-liquid separation, which has the prospect of practical application.
[0016] The present invention has the following advantages: (1) The present invention proposes a method for preparing and applying a polyurethane porous foam-loaded CdS / MIL-101(Fe) photosensitizer, which uses a simple two-step method to synthesize a composite material with high surface area and porosity. The composite material not only provides a larger adsorption bed for reactants, but also excites the photocatalyst to generate photogenerated electrons-holes with long life and redox properties, thereby improving the performance of photocatalytic reduction of CO2 to methanol.
[0017] (2) The supported CdS / MIL-101(Fe) photosensitizer proposed in the present invention can achieve rapid solid-liquid separation. At the same time, the rich pore structure of the polyurethane sponge carrier can effectively increase the loading of active components and promote the improvement of catalytic activity. In addition, the supported catalyst can be regenerated by flushing and can be recycled, and has good stability.
[0018] (3) The CdS / MIL-101(Fe) photocatalytic reaction system constructed by the present invention fully utilizes the structural advantages of MOFs materials to promote the efficient migration of photogenerated electrons at the interface. As the linking center between the photosensitizer CdS and the porous carrier, it can enrich the gaseous reactants at the redox active sites and further avoid the photocorrosion of the photosensitizer, thereby prolonging the reaction activity. DETAILED DESCRIPTION
[0019] The present invention is further described by way of examples.
[0020] Example 1 A polyurethane porous foam-supported CdS / MIL-101 (Fe) photosensitizer utilizes the structure of MOFs materials to enhance the photoinduced electrons generated by CdS to promote the reduction of CO2, and is immobilized on a porous carrier to achieve rapid solid-liquid separation of the catalyst. The preparation is carried out according to the following steps: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, soak it in ultrapure water for 24 hours, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of 1:10 to polyurethane sponge, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 30°C, 150 r / min and 4 h; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 5:1, then add 1 mM thioacetamide solution and 0.05 g of surfactant polyethylene glycol dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, then stand and age at room temperature, and control the water bath temperature and aging time to 80 °C and 3 h; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
[0021] The yield of methanol from photocatalytic reduction of CO2 by the prepared supported photosensitizer is 335 μmol / g.
[0022] Example 2 A polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer is prepared similarly to Example 1 by the following steps: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 hours, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of 1:5 to polyurethane sponge, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 25°C, 150 r / min and 2 h; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 1:1, then add 1 mM thioacetamide solution and 0.05 g of surfactant polyethylene glycol dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, then stand and age at room temperature, control the water bath temperature and aging time to 60 °C and 6 h; (5) After the reaction is completed, the product is washed and dried to obtain a supported CdS / MIL-101(Fe) photosensitizer. The yield of the prepared supported photosensitizer for photocatalytic reduction of CO2 to methanol is 274 μmol / g.
[0023] Example 3 A polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer is prepared similarly to Example 1 by the following steps: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 hours, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of MIL-101(Fe):polyurethane porous foam of 1:15, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 40°C, 200 r / min and 4 h; (3) After the shaking is completed, the polyurethane sponge is taken out, rinsed with ethanol, and dried in an oven to obtain the MIL-101(Fe) supported catalyst for use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 4:1; then add 1 mM thioacetamide solution and 0.05 g surfactant CTAB dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, and then stand at room temperature for aging, controlling the water bath temperature and aging time to 90°C and 4 h; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
[0024] The yield of methanol from photocatalytic reduction of CO2 by the prepared supported photosensitizer is 349 μmol / g.
[0025] Example 4 A polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer is prepared similarly to Example 1 by the following steps: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 hours, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of 1:10 to polyurethane sponge, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 25°C, 200 r / min and 6 h; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 1:1, then add 1 mM thioacetamide solution and 0.05 g of surfactant polyethylene glycol dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, then stand and age at room temperature, control the water bath temperature and aging time to 90 °C and 6 h; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
[0026] The yield of methanol from photocatalytic reduction of CO2 by the prepared supported photosensitizer is 309 μmol / g.
Claims
1. A method for preparing a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer, characterized in that: The structure of MOFs materials is utilized to enhance the photoelectrons generated by CdS to promote the reduction of CO2, and the CdS is immobilized on a porous carrier to achieve rapid solid-liquid separation of the catalyst, including the following steps: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 hours, dry it, and set aside; (2) Dispersing MIL-101(Fe) powder in anhydrous ethanol, and adding the activated polyurethane sponge in (1), wherein the mass ratio of MIL-101(Fe):polyurethane porous foam is 1:(5-20), placing in an ultrasonic reactor for ultrasonic dispersion, and then placing in a constant temperature shaker for oscillation reaction for 2-6 hours, controlling the temperature at 25-40°C, the oscillation rate at 100-250 r / min and the time; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under the condition of heating in a water bath at 60-90°C, the MIL-101(Fe) supported catalyst obtained in (3) was added to the Cd(NO3)2 solution for reaction for 3-6 h, wherein the molar ratio of Cd(NO3)2 to MIL-101(Fe) was (1-8):1; then 1 mM thioacetamide solution and 0.05 g surfactant were added dropwise according to the molar ratio of nCd(NO3)2:nthioacetamide of 1:1, the mixture was stirred for 2 h, and then allowed to stand at room temperature for aging; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
2. The method for preparing a polyurethane porous foam-supported CdS / MIL-101 (Fe) photosensitizer according to claim 1, characterized in that: The surfactant is any one of polyethylene glycol and CTAB.
3. The method for preparing a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer according to claim 1 or 2, characterized in that: Prepare as follows: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 hours, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of 1:10 to polyurethane sponge, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 30°C, 150 r / min and 4 h; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 5:1, then add 1 mM thioacetamide solution and 0.05 g of surfactant polyethylene glycol dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, then stand and age at room temperature, and control the water bath temperature and aging time to 80 °C and 3 h; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
4. The method for preparing a polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer according to claim 1 or 2, characterized in that: Prepare as follows: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 hours, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of 1:5 to polyurethane sponge, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 25°C, 150 r / min and 2 h; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 1:1, then add 1 mM thioacetamide solution and 0.05 g of surfactant polyethylene glycol dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, then stand and age at room temperature, control the water bath temperature and aging time to 60 °C and 6 h; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
5. The method for preparing a polyurethane porous foam-supported CdS / MIL-101 (Fe) photosensitizer according to claim 1 or 2, characterized in that: Prepare as follows: (1) Place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 hours, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of MIL-101(Fe):polyurethane porous foam of 1:15, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 40°C, 200 r / min and 4 h; (3) After the shaking is completed, the polyurethane sponge is taken out, rinsed with ethanol, and dried in an oven to obtain the MIL-101(Fe) supported catalyst for use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 4:1; then add 1 mM thioacetamide solution and 0.05 g surfactant CTAB dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, and then stand at room temperature for aging, controlling the water bath temperature and aging time to 90°C and 4 h; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
6. The method for preparing a polyurethane porous foam-supported CdS / MIL-101 (Fe) photosensitizer according to claim 1 or 2, characterized in that: Prepare according to the following steps: (1) place a 5×5 cm polyurethane sponge cut into a shape in a dry beaker, rinse it with dilute acid, then soak it in ultrapure water for 24 h, dry it, and set aside; (2) MIL-101(Fe) powder was dispersed in anhydrous ethanol at a mass ratio of 1:10 to polyurethane sponge, and the polyurethane sponge activated in (1) was added, and the mixture was placed in an ultrasonic reactor for ultrasonic dispersion, and then placed in a constant temperature shaker for oscillation reaction, and the temperature, oscillation rate and time were controlled at 25°C, 200 r / min and 6 h; (3) After the shaking is completed, take out the polyurethane sponge, rinse it with ethanol, and dry it in an oven for later use; (4) Under water bath heating conditions, add the MIL-101(Fe) supported catalyst obtained in (3) to the Cd(NO3)2 solution at a molar ratio of Cd(NO3)2 to MIL-101(Fe) of 1:1, then add 1 mM thioacetamide solution and 0.05 g of surfactant polyethylene glycol dropwise at a molar ratio of nCd(NO3)2:n thioacetamide of 1:1, stir and mix for 2 h, then stand and age at room temperature, control the water bath temperature and aging time to 90 °C and 6 h; (5) After the reaction is completed, the product is washed and dried to obtain a loaded CdS / MIL-101(Fe) photosensitizer.
7. A polyurethane porous foam-loaded CdS / MIL-101 (Fe) photosensitizer, characterized in that Prepared according to any one of claims 1 to 6.
8. Use of the CdS / MIL-101 (Fe) photosensitizer supported by the polyurethane porous foam according to claim 7 in the photocatalytic reduction of CO2 to produce methanol.